Value optimization of sow byproducts through new business development - Oium-Zube, Teresa (Kansas State University, 2011)
Johnsonville Sausage’s core business is to produce premium fresh and ready to eat (RTE) sausage. To accomplish this on the fresh side of the business, the organization procures and slaughters all of their own animals. The type of animal that Johnsonville Sausage procures is called a “fancy sow”. This type of sow averages 500 pounds and has had three or more litters of piglets. Johnsonville Sausage is the largest procurer of this type of sow accounting for 23% of the overall market. The largest contributor to the finished product cost is the meat. Over the last two years, the organization’s business has been faced with a number of challenges related to mass liquidations within the hog industry as well as increased sow prices due to lower supplies. Specifically, these issues have impacted the expected profitability as an organization and lead Johnsonville Sausage to question whether the supply projections within the industry will meet future growth needs. Because of these factors, Johnsonville Sausage is looking at how they can create more value for the sow that is slaughtered in order to utilize the whole animal to its highest potential, increase overall profitability to the organization and increase available sow supply within the industry. Within the business today, 55% of a sow that is harvested goes towards making the meat formulations (batter) utilized in fresh sausage production. The other 45% of the sow can be broken down into three key areas: sales credits, drop credits and rendering. Items within these three areas are classified as by-products and are sold to industries such as human consumption, pet food, pharmaceutical, medical, academia, commercial fishing and rendering to name a few. The issue that Johnsonville Sausage faces is how to define new channels, create new products, and increase customer base and volume for those parts of the sow that are not utilized in fresh sausage production thus driving increased value for these by-product items. In conjunction with this, how do they create more profitability for those items that are consistently harvested and sold today? The focus of this research was to create a project portfolio for the by-product business within Johnsonville Sausage. The goal of the portfolio was to identify industries and projects that would drive the greatest profit maximization for the by-product business and in return achieve the greatest return per sow. To accomplish this, optimization models and net present value (NPV) analyses were utilized. Utilizing the tools, I found that within Johnsonville Sausage’s existing by-product business, they have the opportunity to increase profitability by 54% from what was achieved in 2010. In conjunction with this, a NPV analysis on a further processed pork loin was conducted. Results of this analysis proved that creating this type of concept for Johnsonville Sausage was a more value added solution financially as compared to the traditional manner in which pork loins are sold today.
Keywords: By-product market; Drop credits; Sales credits; Rendering; Net present value; Sausage business; Agriculture, General (0473); Business (0310); Economics (0501)